PRIORITIZING LEAN TOOLS FOR INTEGRATION WITH INDUSTRY 4.0 TECHNOLOGIES USING A HYBRID FUZZY MOORA APPROACH - Chivukula, Koteswarapavan; Pattanaik, Laxmi Narayan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The fourth industrial revolution, or Industry 4.0 (I4.0), relies on the all-pervasive capability of the internet and digitalization. Key technologies and tools under this are bringing a sea change in manufacturing practices. Lean manufacturing, which has a proven acceptance by manufacturers, is also undergoing this transition marked as Lean 4.0. This paper presents a study on prioritizing various groups of lean tools for this transition based on their basic features and compatibility with I4.0 technologies. A systematic literature review (SLR) is carried out, followed by a thematic analysis to understand the status of this integration based on seven I4.0 technology themes. Priority weightage for six selected I4.0 capabilities is established by mapping with seven major I4.0 enabling technologies based on inputs from twelve industry experts. Four groups of lean tools are formed on various criteria like operation level, data-driven analysis, process design, and system improvement. Using a fuzzy MOORA (Multi-objective Optimization On the basis of Ratio Analysis approach), the rankings for these lean tool groups are found considering the I4.0 capabilities as an attribute along with their priority weightings. A consistency test and sensitivity analysis were carried out to ensure the data's validity and the robustness of the results. Based on the results of this study, compatibility and priority for the potential integration of lean tools and I4.0 technologies are suggested.